Angiotensin Converting Enzyme 2, Angiotensin-(1-7), and Receptor Mas Axis in the Kidney - Sergio Veloso Brant Pinheiro; Ana Cristina Simões e Silva (International Journal of Hypertension)
In the past few years the understanding of the renin-angiotensin system (RAS) has improved, helping to better define the role of this system in physiological conditions and in human diseases. Besides Angiotensin (Ang) II, the biological importance of other Ang fragments was progressively evidenced. In this regard, Angiotensin- (Ang-) (1-7) was recognized as a biologically active product of the RAS cascade with a specific receptor, the G-protein-coupled receptor Mas, and that is mainly formed by the action of the angiotensin-converting enzyme (ACE) homolog enzyme, ACE2, which converts Ang II into Ang-(1-7). Taking into account the biological effects of these two mediators, Ang II and Ang-(1-7), the RAS can be envisioned as a dual function system in which the vasoconstrictor/proliferative or vasodilator/antiproliferative actions are primarily driven by the balance between Ang II and Ang-(1-7), respectively. In this paper, we will discuss our current understanding of the ACE2/Ang-(1-7)/Mas axis of the RAS in renal physiology and in the pathogenesis of primary hypertension and chronic kidney disease.